Impact of changes in the vaginal microbiome and chronic endometritis on the initiation of hyperplastic processes of the endometrium in women - Khaskhachykh, Dmytro; Potapov, Valentin (The Ukrainian Scientific Medical Youth Journal, 2022)
the article presents a review of the literature, which examines the impact of changes in the vaginal microbiome and chronic endometritis on the development of hyperplastic processes of the endometrium in women. Many studies have proven the undoubted role of these factors in the development of endometrial hyperplastic processes, such as atypical hyperplasia and endometrial polyposis. Chronic endometritis, on the background of which there was a course of endometrial hyperplasia, in 95.1% of women studied was caused by an infection of viral, bacterial or fungal origin. Numerous studies indicate the important role of chronic persistent infection in the development of hyperproliferative processes of the endometrium. The largest role in the pathological process is probably played by bacteria of the genus Gardnerella viridans as well as gram-positive cocci (Streptococcus). Herpes simplex virus, cytomegalovirus, human papilloma virus and pathogenic fungi represented by the genus Candida also influence the occurrence of this process. Further studies of the pathological action of these microorganisms will achieve greater accuracy in the diagnosis of hyperplastic processes of the endometrium.